CLASSIFICATION OF MEDICAL DATASET FOR MONITORING AT HOSPITAL EMERGENCY DEPARTMENT USING ARTIFICIAL RABBITS OPTIMIZER WITH MACHINE LEARNING - Dr. G. Krishna Mohan,; Sd. Nafees Ahamed, (Utilitas Mathematica, 2025)
This study meets the immediate want for more precise prediction techniques among the growing global frequency of cardiac disorders. rising numbers of heart-associated diseases name for sophisticated gadgets For early diagnosis and intervention. The importance of this company is seen in its potential to change predictions of heart disease. by allowing quick and focused moves, accurate models can significantly affect public fitness and assist to lessen the increasing load of cardiovascular diseases. Emphasising improved heart disease prediction, the study uses feature engineering techniques and current machine learning algorithms. We seek to discover the maximum a hit approach for correct predictions through comparing fashions including ARO utilising Vnblr, neural networks, decision-making trees, SVM, GBDT, and naive Bayes. The focus on cardiovascular health, which concerns researchers and medical experts, yields advantages for all individuals. Precise prediction models offer a proactive strategy for health care, facilitating targeted interventions and thereby improving outcomes for individuals at risk of cardiovascular disease. Given cardiac issues now rating as the primary purpose of demise globally, the results of this initiative may want to have a primary impact on the scene of global fitness. correct and well timed forecasts enable healthcare structures to deal with the increasing problems related to cardiovascular illnesses. to improve the prognostic powers of our heart ailment prediction model, we've covered ensemble learning techniques as a task extension. In a stacking classifier utilizing a very last LightGBM classifier, the version leverages the strengths of many algorithms to reap advanced accuracy in contrast to triple classification. Combining AdaBoost and Random woodland classifiers, a voting classifier improves model resilience with a tender voting mechanism as properly.